Emphasize The Social Nature of Learning - Abdirakhimova Mokhigul Normurodovna (Zien Journals, 2022)
This article outlines and discusses the Social Nature of Learning as it applies to an overall approach to CLT within second language education and suggests that second language teachers can actively implement more student–student collaboration in their classes so that the students can further develop their second language skills and abilities.
Keywords: Cooperative learning; cooperative skills; Investigation; Planning